THE ROLE OF ANALYSIS FINANCIAL REPORT MANAGEMENT IN INCREASING MSMES INCOMES - Supatmin Supatmin; Paeno Paeno; Sutrisno Sutrisno (Jurnal Ekonomi, 2022)
Financial reports have a significant impact on business unit revenue. where the annual calculation must be reported every financial year. To find out how much spending and income. Corporate financial accounting continues to use logbook attachments and these little notes are used for reference in every business. This study uses a descriptive analytical research method that provides clear, objective, systematic, analytical and critical descriptions and explanations. In this study, primary and secondary methods were used as data collection techniques, collecting data through direct interviews with MSME owners in South Tangerang City and other sources such as writings, articles, writings and journals related to the research topic. All sources are collected and completed according to the needs and objectives of the research. The role of financial reporting in increasing MSME income. Based on research analyzed in South Tangerang City, it shows that financial reporting has a relative influence on income. Where financial reports can improve the performance of business units and the results themselves determine the profit (profit) of the company. There are no financial reports in the City of South Tangerang, so that MSME actors in the City of South Tangerang have difficulty making business decisions. This can affect the company's performance both in determining future costs and in determining future goals.